Pengaruh cadangan devisa, neraca pembayaran, dan jumlah uang beredar terhadap tren nilai tukar rupiah - Aisyah, Dila Nur; Pratomo, Dimas; Supriyaningsih, Okta; Setyanto, Alief Rakhman (Journal of Economics Research and Policy Studies, 2024)
A country is in good condition with its national economy if there are several positive macroeconomic indicators, including increasing foreign exchange reserves, a stable balance of payments, and a decreased amount of money in circulation. This study analyzes the effect of foreign exchange reserves, balance of payments, and the amount of money in circulation of a country on the exchange rate using time series data from 2004 to 2023 and the VECM model. The causality test results did not find a causal relationship between foreign exchange reserves and the exchange rate. At the same time, the balance of payments affected the exchange rate, but not vice versa. In addition, there was no reciprocal influence between the amount of money in circulation and the exchange rate. The results of the VECM test generally show a long-term relationship and an adjustment mechanism from the short term to the long term.